2018
DOI: 10.1002/adfm.201800931
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity Driven by Drug Linker Modification in a Polyglutamic Acid‐Based Combination‐Drug Conjugate

Abstract: Combination nanotherapies for the treatment of breast cancer permits synergistic drug targeting of multiple pathways. However, poor carrier degradability, poor synergism of the combined drugs, low drug release regulation, and a lack of control on final macromolecule solution conformation (which drives the biological fate) limit the application of this strategy. The present study describes the development of a family of drug delivery systems composed of chemotherapeutic (doxorubicin) and endocrine therapy (arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 48 publications
2
29
0
2
Order By: Relevance
“…Therefore, high CAA content of MDA‐MB‐231‐Luc tumors may serve as a faithful model to study this phenomenon and develop treatments to avoid adipocytic protumorigenic effects. Furthermore, high‐lipid content and low‐cellular density in the tumor stroma generated a softer tumor mass with a threefold higher EPR effect, thereby providing a model to assess EPR‐related passive tumor accumulation, especially important for the effectiveness of nanomedicinal approaches to cancer treatment . The flexibility and permeability of the MDA‐MB‐231‐Luc model stroma may also provide a means to assess intratumoral administration strategies …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, high CAA content of MDA‐MB‐231‐Luc tumors may serve as a faithful model to study this phenomenon and develop treatments to avoid adipocytic protumorigenic effects. Furthermore, high‐lipid content and low‐cellular density in the tumor stroma generated a softer tumor mass with a threefold higher EPR effect, thereby providing a model to assess EPR‐related passive tumor accumulation, especially important for the effectiveness of nanomedicinal approaches to cancer treatment . The flexibility and permeability of the MDA‐MB‐231‐Luc model stroma may also provide a means to assess intratumoral administration strategies …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high-lipid content and low-cellular density in the tumor stroma generated a softer tumor mass with a threefold higher EPR effect, thereby providing a model to assess EPR-related passive tumor accumulation, especially important for the effectiveness of nanomedicinal approaches to cancer treatment. 7,30,31 The flexibility and permeability of the MDA-MB-231-Luc model stroma may also provide a means to assess intratumoral administration strategies. 32 The metabolomic comparison of 4T1 and MDA-MB-231-Luc primary tumors suggests that specific metabolic alterations could explain the differences observed in growth rates, with guanosine and uracil (a pyrimidine derivative) the two most relevant soluble metabolites contributing to model discrimination.…”
Section: Modeling Capacities Of the 4t1 And Mda-mb-231-luc Tnbc Modelsmentioning
confidence: 99%
“…[11,12] In addition, it has been observed that nanoparticle properties such as chemistry, size, shape, and aspect ratio all have an effect on pharmacokinetics, tumor penetration and organ accumulation. [13][14][15][16][17] These concepts have been reviewed in recent years due to the importance of achieving the appropriate trade-off between nanoparticle characteristics to achieve both prolonged circulation and good penetration into a solid tumor mass. [18][19][20] However, while there have been investigations of many nanoparticle sizes and shapes, there remain questions relating to how nanoparticles of specific sizes and architectures, but retaining the same surface chemistry behave in in vivo environments.…”
Section: Introductionmentioning
confidence: 99%
“…14 Recent studies have also revealed the promising application potential of polymer-drug conjugates (PDCs) as combination nanomedicines. [15][16][17][18][19][20][21][22] Compared with separate administration of PTX and GEM, integrated single nanomedicine formulations for co-delivery of PTX and GEM can simplify the cancer treatment process. 23 However, there is a vast difference in hydrophobicity between PTX and GEM.…”
Section: Introductionmentioning
confidence: 99%